Harpie, piranie, anioly - Kofta, Krystyna; Domagalik, Malgorzata (Warszawa : Wydawn. W.A.B., 1997)
A conversation between two popular Polish women writers/journalists on aspects of being a woman in Poland.
Keywords: Feminism; Women -- Social conditions; Femininity